Analysis of results of verification of efficiency of process of legal socialization of children-orphans teens in general school, boarding school (Pedagogy of Higher and Secondary Education, 2014)
Sizonenko I. G. Analysis of results of verification of efficiency of process of legal socialization of children-orphans teens in general school, boarding school.In the article the analysis of process of teen-orphans’ legal socialization in boarding-school of general education is presented.
Keywords: model; legal socialization; criteria; indicators of legal socialization; children-orphans; adolescence